77.0k views
1 vote
The second statement

The second statement-example-1
User Vtukhtarov
by
4.6k points

2 Answers

1 vote

Answer: It's a matter of knowing what those words and symbols mean. Read and learn.


Explanation:


Statement 1 is "A⇒B" or "A=>B". It can be read as "A implies B", or "If A then B", or "B only if A." It is also the same as "B or not A," but that is written "B ∨ ¬A" or "B || ~A".


Statement 2 is "B⇒A" or "B=>A". It can be read as "B implies A", or "If B then A", or "A only if B". It is also the same as "A or not B," but that is written "A ∨ ¬B" or "A || ~B".


Choice "D. Contradiction": Eliminated, since statement 2 does not contradict statement 1.


The statement which contradicts "A implies B" is "A does not imply B", or "not (B or not A)" which expands to "A and not B" by DeMorgan's theorem. You must have B false and A true to contradict "A implies B."


Choice "A Inverse": Eliminated for the same reason as choice D.


The "inverse" or "negation" of a logical statement is true whenever the original statement is false, and vice versa. That is to say, one statement is the inverse of another if and only if the two statements contradict one another. Here, statement 2 is not the negation of statement 1. "B implies A" is not the same as "A does not imply B."


Choice "B Contrapositive":

The contrapositive of "A implies B" is "(not B) implies (not A)", or "¬B⇒¬A". The two, "A⇒B" and "¬B⇒¬A", are equivalent: both are true unless B is false and A is true. "A implies B" means "B or not A".

"Not B implies not A" means "not A or not not B," which is the same as "B or not A".


This leaves choice "C: converse" as the correct answer. The converse of statement 1, "A implies B", is "B implies A". When both are true, we say "A if and only if "B.


User SteveDonie
by
5.2k points
5 votes

Answer:

Option C.

Explanation:

Given :

a⇒b

b⇒a

Let p and q be two statements .

Contrapositive :

If not q then not p

Converse :

If p then q

Inverse :

If not p then not q

Contradiction :

In order to prove q is true, we assume p is true . But at the end , we get that what we assumed was wrong i.e we get a contradiction .

In this question as per the above definitions , the two statements are neither contrapositive nor inverse of each other . Also, the two statements also do not contradict each other . As per the definition , they are converse of each other .

User Ogs
by
4.6k points